Placenta Microrna Profile Of Patient With Obstetric Antiphospholipid Syndrome - Muhammad Aliff MOHAMAD; Asral Wirda AHMAD ASNAWI; Muhammad Shazwan SUHIMAN; Jameela SATHAR; Abdul Rahman HAYATI; Nur Syahrina Rahim; Maizatul Azma Masri; Nazefah Abdul Hamid; Samsudin NURUL FARIHAH; Nadeeya'ayn Umaisara Mohamad Nor; Nur Fariha Mohd Manzor (College of Pathologists, Academy of Medicine Malaysia, 2024)
The Malaysian Journal of Pathology, Volume 45 Issue 3 Page (425–440)